Two-dimensional Sparse Antenna Array of a Passive Coherent Radar using a Parametric Algorithm of Signal Processing via the Section Method - V. M. Kutuzov; V. I. Veremyev; M. A. Ovchinnikov; G. V. Komarov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. A two-dimensional configuration of the receiving antenna array (AA) is used to measure the angular coordinates of radar targets – azimuth and elevation. A transformation of one-dimensional uniform AA into a flat two-dimensional AA with a fixed number of antenna elements (AEs) and constant aperture size leads to a nonuniform arrangement of AE in the AA rows. As a result, the AA becomes sparse, which negatively affects the quality of the AA three-dimensional antenna pattern (AP). The section method based on the modified parametric Burg algorithm is a promising and relevant method for constructing directional characteristics. This method can be recommended for spatial processing of reflected signals in a passive coherent radar with a two-dimensional sparse receiving AA.Aim. To analyze the azimuthal and elevation sections of three-dimensional APs obtained using a modified Burg method for spatial processing of reflected signals in a passive coherent radar, the AEs of which are located horizontally and vertically with a step that is a multiple of the half the wavelength λ of the used illumination signal carrier oscillation.Materials and methods. The construction of directional characteristics was implemented via computer simulation in the MATLAB environment with the effect of uncorrelated additive complex normal noise on the receiving channels in each AE as an interference.Results. The possibility and conditions for the application of the modified parametric Burg method in the problems of single signal detecting and angular resolution of equal-power signals in a passive coherent radar, which includes a two-dimensional sparse AA, were determined. The obtained Burg method directional characteristics were compared with the directional characteristics obtained using conventional algorithms based on the discrete Fourier transform. The use of the Burg method allowed the AP side lobe level to be reduced to a practically acceptable level of -12 ... -17 dB at a signal to noise ratio 6 dB. In addition, the Rayleigh resolution of signals in the AA was significantly improved.Conclusion. The presented modified Burg method is suitable for signal processing in two-dimensional sparse AA, subject to restrictions on the AE placing method and the AA aperture size. This allows the Burg method to be recommended for use in passive coherent radars.